O léxico tabu: usos e aspectos socioculturais - Orsi, Vivian [UNESP] (My University, 2013)
The language in use in a society is product of a culture and reflects the way a community thinks. Therefore, the lexical units, through the meanings assigned by a social group, establish a specific look of the universe. We intend to demonstrate that for the denomination of the sexual organs of the human body it usual to avoid the official anatomical terminology – relegated to the contexts of great formality – and to adopt other lexical items during informal situations. This paper reflects about some sociocultural aspects of the forbidden language, that encloses the erogene zones. Using as theory the studies of Lexicology and the obscene lexicon, we intend to verify this lexical typology based in our corpus, and stimulate reflections about the use and the substitution of the official terminology, showing that there are variations in relation to the age and gender of the speakers. We intend, with this research, to demystify some prejudices related to the erotic-obscene lexicon, its use and its creation and to stimulate reflections.

A língua em uso numa sociedade é produto de uma cultura e reflete o pensamento de um povo. Desse modo, as unidades léxicas, por meio dos significados atribuídos por um grupo social, determinam um olhar específico do universo. Intencionamos demonstrar que para a denominação dos órgãos sexuais do corpo humano tende-se a evitar a terminologia anatômica oficial – relegada a contextos de grande formalidade – e adotar outros itens lexicais em situações informais. Este artigo engloba alguns aspectos socioculturais da linguagem proibida referente às zonas erógenas. Utilizando como aporte teórico os estudos sobre Lexicologia e sobre o léxico obsceno, objetivamos verificar essa tipologia lexical utilizando nosso corpus, e suscitar questionamentos sobre o uso e substituição da terminologia oficial por outros itens em situações informais, mostrando que há variação em relação à idade e ao sexo dos falantes. Almejamos com esta pesquisa desmistificar alguns preconceitos relacionados ao léxico erótico-obsceno, seu uso e sua criação e estimular reflexões sobre o mesmo.
The taboo lexicon: uses and sociocultural aspects
Keywords: Lexicologia; Léxico Erótico-Obsceno; Tabu; Sociocultura; lexicology; erotic-obscene lexicon; taboo; socioculture